Strain-Engineering the Anisotropic Electrical Conductance of Few-Layer Black Phosphorus - Fei, Ruixiang; Yang, Li (Nano letters, 2014)
Newly fabricated few-layer black phosphorus and its monolayer structure, phosphorene, are expected to be promising for electronic and optical applications because of their finite direct band gaps and sizable but anisotropic electronic mobility. By first-principles simulations, we show that this unique anisotropic free-carrier mobility can be controlled by using simple strain conditions. With the appropriate biaxial or uniaxial strain (4–6%), we can rotate the preferred conducting direction by 90°. This will be useful for exploring unusual quantum Hall effects and exotic electronic and mechanical applications based on phosphorene.